Ta-Nb AND TR-MINERALIZATION IN MESOZOIC-CENOZOIC SEDIMENTS OF THE UPPER KAMA BASIN AND PERSPECTIVES OF EXPANDING AND DEVELOPMENT OF MINERAL RESOURCES IN THE REGION - Osovetskiy, B.M. (Perm Federal Research Centre Journal, 2014)
The results of investigating Ta-Nb (minerals: ilmenorutile, columbite, Nb-loparite, Nb-ilmenite, Nb-perovskite, Ta-rutile, pyrochlor) and TR (Ce-monazite, florencite, kularite, allanite, Ce-loparite, Ce-perovskite) mineralization in Mesozoic and Cenozoic terrigenous sediments of the Upper Kama basin are presented. The attendant useful minerals are gold, platinum metals, diamond, cassiterite, ilmenite, zircon, rutile, etc. The field expeditions with sampling and enrichment of panning and gross samples on spiral separator or sluice have been carried out. Under laboratory conditions effective express-methods of concentrate processing and selection of placer minerals are applied. The methods of electron microscopy, mineralogical, microprobe, X-ray, diffraction and thermic analysis are used. The perspectives of development of mineral resources in the region are connected with discovering complex placers and simultaneous extraction of precious minerals during exploitation of sandy-gravel deposits .